Kevin Sweeney Leads Fresno State Bulldogs Over Fullerton Titans in Football - Watkins, Howard::::::::: (1986)
Final scoreboard: Fresno State Bulldogs 30 and Fullerton Titans 20; no time on clock Scoreboard ads for Great American Bank and The Fresno Bee